Europe on the road to Doha: towards a new global trade round? - Neary, J (Institute for the Study of Social Change, 2003)
This paper reviews progress towards a new trade agreement under the Doha Development Agenda. A hitherto-unnoticed empirical regularity suggests that post-Cancun pessimism may be unwarranted. Some of the key contentious issues are examined, including agricultural and manufacturing trade barriers, competition policy and intellectual property rights. A potential sticking point is whether the US will accept a quasijudicial role for the WTO and constraints on anti-dumping policy. European governments need to decide how badly they want to complete a new trade agreement, and should start preparing their constituents for compromise if an agreement is to be reached.